Consequences of violence experienced in childhood - Danutė Klokmanienė; Loreta Klokmanienė; Audronė Rimkuvienė (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose)
A family is an institution where a person acquires all social roles and behaviour patterns. One of the main factors destroying a family’s harmony is domestic violence. Violence against children is a relevant issue in all countries. The extent of this problem is increased by the established opinion of society that the family’s problems are only its business. They are not made public, and the family itself must solve the problems within its environment. Empirical data were analysed after conducting qualitative research based on a semi-structured interview, which allowed a better understanding of an individual, delving into her problems and clarifying the need for assistance and its importance in her personal life. Content analysis was applied after conducting the research. The research involved 8 women who experienced various punishments as a means of upbringing in childhood. The research revealed that the causes of violence against children in a close environment often do not depend on children’s behaviour or other characteristics related to them. Violent families often live below the poverty line and have alcohol addiction or other social problems. Parents are usually violent because they were abused as children, and they consider it an acceptable way of communication and parenting. The consequences of violence against children are obvious and range from low self-esteem to self-harm and suicide. Children who have experienced violence in their close environment often become abusers themselves. It has been determined that in their childhood, the respondents who participated in the research experienced all four forms of violence distinguished in the scientific literature: physical, psychological, sexual, and neglect. However, it has been revealed that the majority of the respondents did not seek help because, at the time when they were children, there was little talk about children’s rights and methods of raising children. If corporal punishment occurred, it was considered to be one of the generally used and acceptable methods of raising children.